Incidence of negative appendicectomy: retrospective follow-up of histopathology specimens - Talreja, Deep P.; Bai, Rani; Talreja, Sagar; Al-Amri, Hamed H.; Al Sawafi, Khalid; Waseemul Haque, Parwez; Albatanony, Ayman (International Surgery Journal, 2022)
Background: Diagnosing acute appendicitis (AA) remains challenging in spite of multiple modern diagnostic tools, therefore normal appendices may be removed in some patients thought to have AA. Negative appendectomy remains a concern in current surgical practice. The aim of this study was to determine the rate of negative appendectomy in Ibra hospital in North Sharqiya, Oman. Methods: This is a retrospective analysis of 515 appendectomies carried out at Ibra hospital, North Sharqiya, Oman between January 2019 and December 2021. The final diagnosis was based on histopathology reports which were retrieved. Results: A total of 515 appendectomies were performed during the study period. The mean age of the patients was 22.76 years (range, 10-70 years). Patients older than 12 years represented 81.4% of the study population. Female patients accounted for 47% of all the patients. The negative appendectomy rate (NAR) was 9.7% (50 patients). Out of these 50 negative appendectomies, 24 patients were adult females, 21 were adult males and 5 patients were children (4 female and 1 male). The female sex accounted for 56% of the negative appendectomies. Conclusions: female sex is a risk factor for negative appendicectomy. Most studies have suggested that CT is efficacious only in decreasing the NAR among women; we found that men benefited from CT as well.